2014
DOI: 10.1089/aid.2013.0232
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum of HIV Care in a Veterans' Affairs Clinic

Abstract: The cascade of HIV care in the United States has become a focus for interventions aimed at improving the success of HIV treatment. The Atlanta VA Medical Center (AVAMC) Infectious Disease Clinic (IDC) is an urban clinic that provides care for over 1,400 people living with HIV (PLHIV) annually. Using data from the HIV Atlanta VA Cohort Study (HAVACS), we modeled the continuum of care in the AVAMC IDC and explored similarities and differences with national models. We conducted a cross-sectional analysis of 1,474… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 14 publications
0
22
2
Order By: Relevance
“…4,8 It has also been demonstrated that clinics with highly integrated healthcare systems (such as the VA system) can attain even greater engagement at each of the stages of care, when compared to these national estimates. 14 In contrast, our study revealed that engagement in care was lower in comparison to previous studies. We found that only 72% of those receiving HIV-related medical care were prescribed ARV, a finding that is similar to estimates modeled by Gardner et al 6 Although this finding is likely attributed to our broader scope of outpatient facilities, it may also be a reflection of low ARV treatment utilization in nonspecialty clinics.…”
Section: Discussioncontrasting
confidence: 99%
“…4,8 It has also been demonstrated that clinics with highly integrated healthcare systems (such as the VA system) can attain even greater engagement at each of the stages of care, when compared to these national estimates. 14 In contrast, our study revealed that engagement in care was lower in comparison to previous studies. We found that only 72% of those receiving HIV-related medical care were prescribed ARV, a finding that is similar to estimates modeled by Gardner et al 6 Although this finding is likely attributed to our broader scope of outpatient facilities, it may also be a reflection of low ARV treatment utilization in nonspecialty clinics.…”
Section: Discussioncontrasting
confidence: 99%
“…21 Similarly, the VA has reported high rates of virologic suppression with the reduction of institutional barriers to care and treatment. 22 An analysis of the Ryan White Program in 2011 also suggested high rates of virologic suppression among patients retained in care 23 but this study also reminds us that retention in care is challenging, particularly for individuals aged 13 – 34 years.…”
Section: Current Status Of Hiv Continuum Of Care Research In the Unitmentioning
confidence: 65%
“…In most continuum models, the presumption is that those represented in the numerator of one step of necessity were in the numerator of the prior step. Yet, Magnal et al identified individuals in an HIV continuum analysis who did in fact meet definitions for having been prescribed ART or even being virologically suppressed but did not meet definitions for having been retained in care (24). In their comparison, categorization of continuum stages as dependent subsets of prior stages led to underestimates of those prescribed ART or achieving viral suppression.…”
Section: Resultsmentioning
confidence: 99%